2017
DOI: 10.15171/bi.2017.22
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum induces apoptosis in oral cancer KB cells through upregulation of PTEN and downregulation of MAPK signalling pathways

Abstract: Introduction: The oral tumor is the sixth most prevalent type of cancer worldwide and the second leading cause of cancer-related mortality. Although chemotherapy and immunotherapy are the main strategies for the treatment of oral cancer, an emergence of inevitable resistance to these treatment modalities is the major drawback that causes recurrence of the disease. Nowadays, probiotics have been suggested as adjunctive and complementary treatment modalities for improving the impacts of chemotherapy and immunoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…In addition to cervical cancer, Lactobacillus is associated with the proliferation and regulation of cells of other cancer types, such as breast cancer, 32 colorectal cancer, 33 gastric cancer, 34 and oral cancer. 35 , 36 Observations in these other cancers may offer insights into the study of Lactobacillus in cervical cancer. The main observations regarding Lactobacillus in cancers are as follows: 1) Lactobacillus can activate and strengthen the antitumor effects of immunocytes such as thymus-derived cells (T cells), natural killer (NK) cells, dendritic cells (DCs), and macrophages and immunological factors produced by immunocytes; 37 – 39 2) a large amount of unmethylated dinucleotide repeat sequences present in the nuclei of Lactobacillus can activate the innate immune response by binding to a specific receptor that exists on the surface of human cells; 40 3) Lactobacillus that is suitable for reproduction and growth in an anaerobic environment can selectively accumulate in the hypoxic zones of solid cancers; 41 and 4) Lactobacillus can selectively locate to solid cancers and can be used as a vector for gene therapy and targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cervical cancer, Lactobacillus is associated with the proliferation and regulation of cells of other cancer types, such as breast cancer, 32 colorectal cancer, 33 gastric cancer, 34 and oral cancer. 35 , 36 Observations in these other cancers may offer insights into the study of Lactobacillus in cervical cancer. The main observations regarding Lactobacillus in cancers are as follows: 1) Lactobacillus can activate and strengthen the antitumor effects of immunocytes such as thymus-derived cells (T cells), natural killer (NK) cells, dendritic cells (DCs), and macrophages and immunological factors produced by immunocytes; 37 – 39 2) a large amount of unmethylated dinucleotide repeat sequences present in the nuclei of Lactobacillus can activate the innate immune response by binding to a specific receptor that exists on the surface of human cells; 40 3) Lactobacillus that is suitable for reproduction and growth in an anaerobic environment can selectively accumulate in the hypoxic zones of solid cancers; 41 and 4) Lactobacillus can selectively locate to solid cancers and can be used as a vector for gene therapy and targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in a synergistic manner, LGG intensified the antineoplastic action of geniposide, supporting the tentative use of this combined therapy also in clinical practice. In another study, Asoudeh-Fard et al (196) demonstrated that Lactobacillus plantarum was able to inhibit and activate the MAPKs and PTEN pathways, respectively, playing a potential role in the regulation of cancer. Indeed, it is well known that PTEN and MAPKs are associated with the inhibition and the initiation of cancer development, respectively (196).…”
Section: Anti-tumoral Effects Of Probioticsmentioning
confidence: 99%
“…In another study, Asoudeh-Fard et al (196) demonstrated that Lactobacillus plantarum was able to inhibit and activate the MAPKs and PTEN pathways, respectively, playing a potential role in the regulation of cancer. Indeed, it is well known that PTEN and MAPKs are associated with the inhibition and the initiation of cancer development, respectively (196). Consequently, a possible use of L. plantarum for probiotics cancer therapy was proposed.…”
Section: Anti-tumoral Effects Of Probioticsmentioning
confidence: 99%
“…Similarly, the authors reported that the probiotic bacterium could increase the expression level of the PTEN gene and subsequently diminish the cancer cells. 35 Moreover, it has been reported that the inactivation of PTEN in the head and neck squamous cell carcinoma cancer cell line can increase the expression of AKT gene and suppress the p53 gene. Indeed, over-expression of the PTEN gene can significantly inhibit the growth of the tumor.…”
Section: Discussionmentioning
confidence: 99%